Muscle Oximetry in Sports Science: A Systematic Review - Perrey, Stephane; Ferrari, Marco (Sports medicine (Auckland), 2018)
Background Since the introduction (in 2006) of commercially available portable wireless muscle oximeters, the use of muscle near-infrared spectroscopy (NIRS) technology is gaining in popularity as an application to observe changes in muscle metabolism and muscle oxygenation during and after exercise or training interventions in both laboratory and applied sports settings. Objectives The objectives of this systematic review were to highlight the application of muscle oximetry in evaluating oxidative skeletal muscle performance to sport activities and emphasize how this technology has been applied to exercise and training. Methods Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were followed in a systematic fashion to search, assess and synthesize existing literature on this topic. The Scopus and MEDLINE/PubMed electronic databases were searched to 1 March 2017. Potential inclusions were screened against eligibility criteria relating to recreationally trained to elite athletes, with or without training programs, who must have assessed physiological variables monitored by commercial oximeters or NIRS instrumentation. Results Of the 14,609 identified records, only 57 studies met the eligibility criteria. This systematic review highlighted a number of key findings in 16 sporting activities. Overall, NIRS information can be used as a marker of skeletal muscle oxidative capacity and for analyzing muscle performance factors. Conclusions Although NIRS instrumentation is promising in evaluating oxidative skeletal muscle performance when used in sport settings, there is still the need for further instrumental development and randomized/longitudinal trials to support the detailed advantages of muscle oximetry utilization in sports science.